Perceptions from employers and graduates about UACJ’s Seguridad y Políticas Públicas program - Valles Devora, Guadalupe; Martínez Almanza, María Teresa (IE Revista de Investigación Educativa de la REDIECH, 2021)
This work emerges from the interest of deepening the knowledge of graduates and employers’ perceptions related to public, private and industrial security on the professional profile of the academic program in Security and Public Policies. 14 semi-structured interviews were applied in which six students from the last semesters of the program and eight employers from different companies participated. The results reveal that thanks to the dissemination through the university’s media channels, there is a degree of knowledge of the program, however the challenges facing graduates do not cease to exist, for example the need of the English language. It is concluded that the program has the required bases that allow university students to position themselves in managerial positions where they will apply the knowledge obtained during their training process within the degree.